Examining The Critical Role of Working Capital Management and Capital Structure on Financial Performance of Manufacturing Firms: An Empirical Assessment - Muhammad Ali Mufti; Zulfiqar Hussain Awan; Javeria Islam (International Journal of Business and Economic Affairs, 2023)
This research aims to examine the relationship between working capital management, capital structure decisions, and financial performance of manufacturing firms listed on the Pakistan Stock Exchange. The study aims to fill the gap in the literature by exploring the impact of various working capital components and capital structure choices on firm profitability and shareholder wealth. The study employs panel data regression analysis to investigate the relationship between observed variables. The data for the study is collected from secondary sources, primarily annual reports of listed manufacturing companies, and covers a six-year period from 2017 to 2022. The study finds that working capital management, as measured by metrics like current ratio, average collection period, and cash conversion cycle, significantly impacts the firm’s economic value added (EVA) and Tobin’s Q. Capital structure decisions, particularly leverage, also have a significant effect on the firm’s performance. However, sales growth does not show a significant impact on the firm’s performance. The study highlights the importance of effective working capital management and capital structure decisions for manufacturing firms’ financial performance and shareholder value. Policymakers, investors, and business owners need to consider these factors while assessing and managing the performance of manufacturing companies. The research is limited to the manufacturing sector and considers data from the Pakistan Stock Exchange. Generalizations to other industries or regions should be made with caution. Additionally, the study uses financial indicators like EVA and Tobin’s Q as proxies for performance, which may not capture all aspects of a firm’s success.